Performance indicators and functional adaptive windows in competitive cyclists: effect of one-year strength and conditioning training programme - Leonardo Cesanelli; Achraf Ammar; Jorge Arede; Julio Calleja-González; Nuno Leite (Termedia Publishing House, 2021)
Changes and relationships between cycling performance indicators following a one-year strength and conditioning training have not been totally clarified. The aims of this study are to investigate (i) the effect of a combined one-year strength and conditioning training programme on performance indicators and the possible relationships between these indicators, and (ii) the existence of possible endurance-functional-adaptive windows (EFAWs) linked to changes in muscular strength and body composition markers. Functional and lactate threshold power (FTP and LTP), maximal strength (1RM) and body composition (body mass index [BMI], body cell mass [BCM] and phase angle [PA]) were measured at the beginning and the end of a one-year strength and conditioning training programme of thirty cyclists. Correlations, differences, and predictive analysis were performed among parameters. Significant differences were found between pre- and post-conditioning programme results for FTP, LTP, 1RM (p < 0.0001) and BCM (p = 0.038). When expressed as power output (W), FTP and LTP were significantly correlated with 1RM (r = 0.36, p = 0.005 and r = 0.37, p = 0.004, respectively), body mass (r = 0.30 and p = 0.02), BCM (r = 0.68, p < 0.001) and PA (r = 0.42 and 0.39, respectively and p < 0.001). When expressed as W·kg-¹, these power thresholds were strongly correlated with body mass (r = -0.56 and -0.61, respectively) and BMI (r = -0.57 and -0.61 respectively) with p < 0.001. Predictive polynomial regressions revealed possible endurance and strength adaptation zones. The present findings indicated beneficial impacts of one-year strength and conditioning training on cycling performance indicators, confirmed the correlation between performance indicators, and suggested the existence of different EFAWs. Strategies aiming to improve performance should consider cyclist characteristics and performance goals to achieve EFAWs and thereby enhance cycling performance.